How environmental regulation will impact Ferrari N.V. in Europe and US - Alves, João Maria Santos Matos (2020)
The following report has the objective to determine the value of fines applied to the Italian luxury car brand Ferrari N.V. pursuant to the current environmental regulation in Europe and US. The outcome of this dissertation will establish a target share price and a finalized investment recommendation. Currently, Ferrari benefits from certain legislations which exempt the brand from specific eco- metrics since it qualifies as a Small Volume Manufacturer in most of the territories where it sells cars. Heavy fines are applied to OEMs that do not comply with emission targets defined in their jurisdictions.